Toward manipulating serotonin signaling via the microbiota–gut–brain axis. (December 2022) - Everett, Blake A; Tran, Peter; Prindle, Arthur
Abstract : It is now well established in humans that there is a bidirectional pathway of communication between the central and enteric nervous systems in which members of the microbiome participate. This microbiota–gut–brain axis (MGBA) is crucial for normal development and physiology, and its dysregulation has been implicated in a range of neurological and intestinal disorders. Investigations into the mechanistic underpinnings of the MGBA have identified serotonin as a molecule of particular interest. In this review, we highlight recent advances toward understanding the role of endogenous serotonin in microbial communities, how microbial communities bidirectionally interact with host serotonin, and potential future engineering opportunities to leverage these novel mechanisms for biomedical applications. Graphical Abstract: ga1 Highlights: Serotonin can interact with bacterial proteins with a range of effects. Serotonin is used in signaling between members of the microbiome and host. Microbiome dysbiosis is associated with many diseases that feature altered serotonin. Advances in probiotic engineering could be used to regulate host serotonin levels.